The Effect of Excellent Service with the A6 Concept on Student Satisfaction at SMK Negeri 7 Makassar - Haerul Haerul; Indah Purnama Sari; Risma Niswaty (Pinisi Journal of Education and Management, 2023)
Excellent service is a service that prioritizes the interests of customers or students. Service providers must be able to provide good service quality standards that exceed the expectations of students so that the needs, desires and expectations of students are met. This study aims to determine the picture of excellent service with the A6 concept, the picture of student satisfaction, and the influence of excellent service with the A6 concept on student satisfaction at SMK Negeri 7 Makassar. This research is a quantitative research that shows cause-and-effect relationships. The sample in this study amounted to 85 students with stratified random sampling techniques. The data collection techniques used are questionnaires, observations and documentation. The data analysis techniques used in this study are descriptive statistical analysis and inferential statistical analysis. The results showed that the variables of excellent service at SMK Negeri 7 Makassar were in the very good category with indicators, namely ability, attitude, appearance, attention, action, and accountability, while the variables of student satisfaction were in the very good category with indicators of speed, accuracy, safety, friendliness, and comfort. Based on the results of the product moment correlation test, the relationship between variables is moderate. Based on the results of a simple linear regression analysis, it was concluded that there was a positive and significant influence of excellent service with the A6 concept on student satisfaction at SMK Negeri 7 Makassar. This research uses the A6 concept as the basis for excellent service to provide satisfaction to students so that the needs, desires or expectations of students are met.